Multilateral regulation of investment - Multilateral regulation of investment (Symposium) (1999 Apr : Leiden, the Netherlands); Nieuwenhuys, E. C (Eva Constant), 1951-; Brus, M. M. T. A.; EM Meijers Institute of Legal Studies (Boston : Kluwer Law International, 2001)
The book presents the incisive views of nine outstanding authorities, both academics and practitoners, in disciplines related to investment and development.
Includes index.
rua 24/08/15
Loans
Keywords: Investments, Foreign -- Law and legislation -- Congresses; multilateral regulation; investment